Avnik demir cevherlerinden hazırlanan peletlerin indirgeme davranışlarına CaO, Na2O ve K20'in etkisi - Şeşen, Mustafa Kelami (Fen Bilimleri Enstitüsü, 1986)
Bu çalışmada, Avnik demir cevherleri harman konsantre¬ sinden hazırlanan peletlerin, çeşitli oranlarda CaO, Na2O ve K2O içermesi halinde göstereceği indirgenme davranışlarını belirlemek amaçlanmıştır. Deneylerde CaO, Na2O ve K2O'in etkilerinin açık bir şekilde görülebilmesi için, alkali içerikli Avnik/Bingöl bölgesi cevherlerinden zenginleştirilen, de¬ mir tenoru yüksek konsantre kullanılmıştır. Bu konsantreden, ilave yapılmadan olduğu^gibi veya çeşitli ilaveler yapılarak, çapı yüksekliğine eşit silindirik özel briket peletler hazırlanarak deneylerde kullanılmıştır. İndirgenme deneyleri, laboratuvar imkanları ile geliştirilmiş, bir terazi ile ağırlık değişimi izlenebilen indirgeme cihazında, hidrojen gazıyla yapılmıştır. Deneylerle, alkali içermeyen ve çeşitli oranlarda Na2Û ve K2Ö gibi alkali ve CaO içeren harmanlarla hazırlanan demir oksit peletlerin indirgenme davranışları; indirgenme hızları, şişme oranları ve indirgenme biçimleri yönlerinden incelenmiştir. Gaz akış hızı, indirgeme sıcaklığı gibi seçilen deney koşullarının ve porozite gibi pelete ait fiziksel özelliğin indirgenme hızının fonksiyonu olduğunun belirlenmesinden sonra, 900°C'de 120 cm3/dak. hidrojen akış hızında % 30 poroziteye sahip pelet- lerle yapılan indirgeme deneyleriyle, peletin bileşimiyle ilgili farklı ve orjinal sonuçlar elde edilmiştir: ilavesiz konsantre ile ve CaO ilaveli harmanla hazırlanan demir, oksit peletler topokimyasal biçimde indirgenme göstermişlerdir, indirgenme; peletteki hematitin bütünü daha düşük oksijen potansiyeline sahip oksitlere (manyetit ve wüs- tit) dönüştükten sonra, hem pelet genelinde, hem de tane düzeyinde dıştan içe doğru metalik demirin oluşumu ile ilerlediği gözlenmiştir. Bu peletlerde topokimyasal indirgenme şeklinden dolayı, metal/oksit faz sınırı arayüzeyi, indirgenmenin ilerlemesiyle küçüldüğünden, indirgenmenin oranı arttıkça indirgenme hızı düşmektedir. Yine bu peletler indirgenme sırasında, topokimyasal indirgenmeden dolayı düşük düzeyde kalan kabul edilebilir ölçüde normal şişme göstermişlerdir. Konsantreye CaO ilave edilerek hazırlanan peletlerde, indirgenme hızının, CaO içeriği veya baziklik oranı ile doğrusal ilişkisi olmadığı saptanmıştır, indirgenme hızı, baziklik oranını yaklaşık l yapan değere kadarki CaO ilaveleri ile düşmüştür. Baziklik oranının l'in üzerine çıkmasıyla indirgenme hızının yeniden artmaya başladığı görülmüştür. Ancak ilavesiz peletlerin üzerinde indirgenme hızına erişilebilmeği için, baziklik oranının; bir miktar kalsiyum ferriti oluşturabilecek değerlere çıkarılması gerektiği saptanmıştır. - iv - Konsantreye Ha2® ve K£0 ilave edilerek hazırlanan peletlerin indirgenmesinde, Na2Û ve/veya K2Û içeriğinin, demir oksit peletlerin indirgenmesini, CaO'den farklı olarak, düşük oranlarda dahi hızlandırdıkları görülmüştür. Ayrıca Na20 ve/ veya K20; demir oksit peletlerin indirgenme sırasında anormal şişmelerine neden olmuşlardır. Düşük oranda SİÛ2 içeren (% 1,7) peletlerde yaklaşık % 0,3 alkali oksit oranı, normal şişme limitinin (% 25) üzerinde şişmeye neden olmuşlardır. Peletlerde Na2Û ve/veya K2Û oranının artmasıyla şişme de artmıştır ve belli oranın ürerinde çatlama ve parçalanma ile devam ederek % 200'lere ulaşmıştır, indirgenme hızı ve şişme¬ de, K2^'in Na2Ûfdan daha etkili olduğu gözlenmiştir. Na2Û ve/veya K2Û içeren demir oksit peletler ilavesiz peletlerden tamamen farklı olarak ilerleyen cephe şeklinde değil, tüm kitlede ünifortn iç indirgenme biçiminde indirgenmişlerdir. Na2O ve/veya K2O'in demir oksit peletlerin anormal şişmesine neden olan olumsuz.etkileri, pelet harmanının Sİ02 içeriği, alkali oksit miktarının ağırlıkça yaklaşık A katına çıkarılarak önlenebilmiştir. SİÛ2 miktarı arttırılan, alkali oksit içerikli bu peletlerin indirgenmesinde katı fazın yayınması önemli rol oynamaktadır. Bu peletlerin indirgenmesi sırasında indirgenen metalik demir, belli yerlerde oluşan çekirdeklere yayınarak demir iğneleri (vhiskers) oluşturacak şekilde büyümüşlerdir.

The structure and composition of iron ores show a wide range of variations. Consequently, especially during the reduction in the blast furnace, the iron ores behave di f f erently. The type and the amount of gang minerale present in the iron ores can effect the reduction behaviour of iron r oxides in different ways and levels. in general, the effects to the behavior of iron raw raaterials during reduction of alkaline and alkaline earth oxides such as Na«0, K«0, CaO are known to be strong and similar. But, vhile the existance of Na O and K?0 are regarded undesirable due to causing the excessive svelling and breakdovn of iron charge materials during reduction, the presence of CaO at certain amounts is desirable. Furthermore, in contrast to CaO, the Na2Û and ^^ circulate in the blast furnace forming scaffolds on the walls of furnace and thus preventing the proper working of the f u rnace. The purpose of this study was to investigate the changes in the reduction behaviour of pellets prepared from ~ vi - iron öre concentrates containing different percentages of CaO, Na20 and K20. in order to be able to observe the effects of additions clearly, magnetite concentrates quite rich in iron, prepared from the alkali containing ores of Avnik/Bin- göl area were used. Cylindrical pellets (14 mm diameter, 1.4 mm height), whose phisical properties could be kept under control, vere produced by blending the above oxides with the concentrate in suitable forms. Since Na.O and K20 could not be added directly, their addition was achieved by first sintering their carbonates at their melting temperatures together with the iron öre con¬ centrates. The cylindrical pellets thus prepared vere fired at 1250 C, and then used in reduction experitnents.,The reduction tests vere conducted vith hydrogen gas. The apparatus developed for this purpose vas incorperated vith a system of thermogravimetriç analysis to follov the veight changes. The reduction rates and the svelling ratios vere studied as a function of composition of pellets by usinğ pellets free of alkalines and pellets containing various amounts of Na~0, K?0 and CaO. in order to establish the direction of the effects of the external reaction conditions HtıH» n» p;ns fi.ov rate and reduction tempernture as veli as of the effect of physical properties such as porosity ete, depending on sample alone, at first tests vere carried out by using pellet samples of constant composition free of any addi ti ons. After having established the fact that the rate of - vii - reduction is a function of the gas flow rate, reduction tem-. perature and the porosity of pellets, the folloving results were obtained f rom the experiments, carried out at 900°C 3 using a gas flow rate of 120 cm /min with pellets having 30 % porosity: >»' 1- The pellets prepared from the original concentrate without any additions, exhibited a topochemical mode of rrdnrtion, Tt was observed that at the first stages of reduct¬ ion hematite is reduced to lower oxides (magnetite, wustite) of lower oxygen potentials. At this stage, the rate of format- ion of metallic iron is very low. But, at later stages, the reduction to the metallic iron starts from the outer parts towards the inner parts of the individual particles, so that a general,simultaneous reduction of the overall pellet takes place from outer to the inner parts of each partide of the pellet. 2- in the pellet samples with basic CaO additives (at 1,4 basicity ratio), the mode of reduction was also topo¬ chemical. But, in these specimens a partial internal reduct¬ ion was observed in front of the metall is ation boundary vithin the pellet. 3- in the pellets reduced topochemically, the rate of reduction decreases with increasing amount of reduced oxide, due to the diminishing interfacial surface area at the metal/ oxide phase boundary resulting from the progress of the reduc¬ tion process. 4- it has been observed that in the pellet samples - vii i - containing low levels of CaO additions (i e. basicity ratio of 0,56-0,98) the amount of slag phase is relatively increased which results a decrease in the rate of reduction, vithout any ot h o. r not L c ca b l. e ti i f f erence. 5- The improvement of the reduction rate of iron oxide pellets by CaO additions is rioticed above a basicity ratio of 1. But, in order to reach a reduction rate above that of pellets containing no-additives, the basicity ratio-muş t be increased to the levels enabling the formation of some cal- cium f errite. 6- Both the pellets containing no additions and pellets with CaO additions have exhibited normal swelling during their reduction as a iron oxides. But in the pellets with CaO additions, the swelling ratio is increased s lightly-less than the normal svelling limit of 25 %-. When the basicity is \ increased slightlyfurther. 7- The presence of Na?0 and K?0 increased the rate of reduction of iron oxide pellets as well as caused abnormal (excessive) svelling. 8- iron oxide pellets containing low percentages of SiO (ie. 1,7 %) showed a svelling above the normal svelling limit of 25 %, when the Na20 and/or K20 amount vere more than 0,3 %. As the Na?0 and/or K20 concentration is further increased, the svelling ratio is also raised finally leading to the fracture and frağmentation of the pellets. 9- Pellets containing more than a certain level of K?0 and/or Na?0 (^0,5 % <) showed a rapid increase in svelling - ıx - at 40-60 % of the reduction. This result implies that the excessive swelling caused by the alkalies. Occur during the transformation from wustite to metallic iron which is the final half stage öf the reduction process. This also explains the whisher type of growth of metallic iron being caused by the excessive swelling. 10- K with is larger ionic diameter is more effective than Na both on the rate of reduction of iron oxide pellets and on their excessive swelling during reduction. 11- The undesirable effects of Na^O and/or K"0 in causing excessive swelling of iron oxide pellets could be prevented by increasing the Si0? content of the pellet blend. In order to stop excessive swelling, the level of SiO must be high enough to bind the ferrites with the alkalies to form a complex oxide as Na_0. Fe?0. 4Si0_ (acmite). Although the above findings do not contradict alto gether the published results in the literature, they show that CaO and Na"0, K-0 have dissimilar influence with regards to excessive swelling. The literature, however, claims that CaO, Na20 and K20 have similar effects to excessive swelling by causing metallic iron to grow as whishers during the reduction. Furthermore, a view held in the literature that the homogeneous distribution of the oxides through high temperature firing can prevent swelling, brings to mind the question of why K?0 and Na20 are not distributed homogeneously at the same high temperature. In this case Na20 and K20 are expected to have a different effect than that of CaO. - x - The distinctive effect of Na 0 and K-0 on increasing the swelling which differentiates it from that of CaO may be a result of partial formation of low melting point liquid slag within the pellets during reduction reactions at around 900 C. The formation and subsequent propagation of small cracks associated with reduction process are then easily increased and further expanded as the pressure is raised during the growth of ferrite as whiskers.
The Effect of CaO, Na2O and K2O to the reduction behaviour of pellets prepared from avnik iron ores
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1986
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1986
Keywords: Demir oksitler; Peletleme; Cevher hazırlama; Iron oxides; Pelletizing; Ore-dressing